1246. Acinetobacter baumannii in the Post-Acute Care Setting: Prevalence and Resistance Rates in Patients, Health Care Personnel and the Environment. (26th November 2018) - Cassone, Marco; Zhu, Ziwei; Gibson, Kristen; Lansing, Bonnie; Cao, Jie; Mody, Lona
Abstract: Background: Acinetobacter baumannii is an important agent of healthcare-acquired infections, sporting high resistance to major antibiotics in acute care. Since A. baumannii is an opportunistic pathogen commonly found in the environment, we aimed to investigate: (1) its prevalence as colonizer on patients, environment, and healthcare personnel (HCP) in Nursing Facilities (NFs) with intermediate intensity of care but high antibiotic pressure and (2) whether resistance rates in colonizing strains vary between patient, environmental, and HCP isolates. Methods: We analyzed A. baumannii patient and HCP colonization and environmental contamination in six NFs in Michigan. Samples were collected from HCPs hands, and from multiple patient body sites and high-touch surfaces at admission, 14 days, and monthly up to 6 months. Ciprofloxacin, imipenem, and ceftazidime resistance was tested according to CLSI guidelines. Results: 651 patients were screened (average follow-up time was 29 days). Patient colonization with A. baumannii was found in 59/1, 620 (3.64%) of visits, and environmental contamination in 267/1, 620 visits (16.48%) ( P < 0.001). Interestingly, HCP showed at least as high or possibly higher colonization rates than patients (32/574) (5.25%) ( P = 0.06). Resistance rates differed significantly between HCP, environmental, and patient isolates, ranging from 35 to 38% for patient isolates, 26 to 30% for environmental isolates, and only 8 to 17% for HCP isolates (table). Conclusion: In our NFs, A. baumannii is more likely to be found on HCPs than on patients. However, HCP isolates have much lower resistance rates. Environmental contamination is alarmingly common, with worrisome resistance rates even in post-acute care settings. Disclosures: All authors: No reported disclosures.